A review of chemical viscosity reducers for heavy oil: Advances and application strategies - Chenhao Gao; Ruiying Xiong; Jixiang Guo; Wyclif Kiyingi; Hanxuan Song; Li Wang; Wenlong Zhang; Xiangwei Chen (Fuel Processing Technology)
The proportion of heavy oil in oil production will be higher and higher, but the high viscosity of heavy oil limits the development of heavy oil. In order to avoid the problems of high energy consumption and carbon emission caused by thermal recovery of heavy oil, this paper reviews and puts forward the application strategy of viscous reducers. By summarizing the thickening mechanism of heavy oil, the viscosity reducing principle, classification, advantages and disadvantages and application range of different viscosity reducers were clarified. The research and development ideas of each viscosity reducers to achieve green circulation were emphatically reviewed. Secondly, the application ideas of wellbore and formation viscosity reduction are given. Finally, from the thickening mechanism of heavy oil and the development, cost and post-treatment of viscosity reducer, the future development direction of viscosity reducer is forecasted.